The iSpring Ebook Learning Media for Online Learning Physics: In Case for Improving Student Conceptual Understanding - Yosef Mikel Kobesi; Warsono Warsono; Rizky Zakwandi; Fajar Kurnianto (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
This study is aimed to determine the effect of learning media, an iSpring e-book, on online learning physics. There are 61 science students of Noemuti State High School participated in this study. The research was used the R&D method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). In the implementation stages, two classes were used in the design quasi-experimental method. Students in the model class are not used iSpring e-book media, while a student in the implementation class used iSpring e-book media. The data in this study were judgments of the feasibility analysis of e-book media using the reproducibility coefficient (Cr). Analysis of differences in concept understanding and interest using N-Gain and effect size d'Cohen. As for the analysis of success indicators using SPSS version 25.0. The results of the validity of the e-book media instrument are feasible with Cr > 0.90. The result of paired sample t-test for both model and implementation classes is the value of t table > t count so that the hypothesis is accepted (Ha) there is a difference between the pretest-posttest values. The results of the analysis of the concept understanding indicators for the implementation class show the interpreting dimension of 91.30 and exemplifying 82.61 with a very good category, while the dimension model class interprets 47.36 with a sufficient category and gives an example of 60.53 good. The results of the analysis of learning interest in the implementation class for the dimensions of feeling happy are 3.56 (high) and involvement 3.69 (very high), while the model class for interest in learning for the dimensions of feeling happy is 3.21 (enough) and involvement is 3.07 (enough). Even though the facilities are constrained, Noemuti High School students are still enthusiastic about taking physics lessons online.